Semantic Structure of Process Verbs in Minangkabau Language - Raees Narhan; mulyadi (Center of Language and Cultural Studies, 2024)
Verbs will be examined through an interrogative construction, which will elicit the states, processes, and actions of verb members in sequence to analyze the proper identification of verb membership. This research is a qualitative descriptive study. Through the use of semantic analysis, this study aims to investigate and describe process verbs in the Minangkabau language. Semantic investigation relates to the roles played by each filler in these functions. The information presented in this paper is based on oral interviews and written data. The primary data source is oral information from Minangkabau dialect informants. The semantic features of process verbs are [+dynamic], indicating the subtypes of event, [+punctual], indicating non-agentive motion subtypes, and [-punctual], indicating process verbs of enduring events. It can be concluded that process verbs in Minangkabau possess semantic components that are [+dynamic] and [+/- punctual]. The semantic structure of Minangkabau process verbs can be explained in their original sense, which serves as the basis for their construction. Process verbs are constructed from the words